Απεικονίσεις κοσμικών κτιρίων σε φορητές εικόνες του 17ου – 18ου αιώνα από το ΄Αγιον ΄Ορος [M. TSIAPALIS, The dipiction of buildings in postable icons of the 17th-18th century] - Τσιάπαλη Μαρίζα (Μακεδονικά, 2011)
The background of a portable icon is filled with buildings very often. Theprevailing items of architecture depicted, are monumental buildings with twoor three floors, towers and many windows, arches and gates, domed churchesor entire towns. In several buildings, the arrangement of the architecturalelements is made in an unusual way, so that they seem to have no functionaluse. The exterior walls of a certain number of buildings are often richlyornamented with floral or geometric patterns. Also, the illustration of otherbuildings is influenced by Italian works.In comparison the buildings depicted in portable icons with those preserved all over Greece since 15th century (Mistras, Kastoria, Veria, Epirus),it could be noted that there are certain resemblances among them. But,although the painters try to imitate the real buildings, usually their depictionscan’t reproduce the reality and just reveal painters’ personal preferences tothe architectural items.